👤

Bonjour,pouriez vous m'aider s'il vous plaît
Développer et réduire les expressions suivantes.
A=(7x+3)(x+5)
B=(5-2x)(3x-6)
C=(3x+1)(-5x+3)
D=6(x+3)+(2x-3)(3x-5)
E=(8-3x)(4x+1)-x(x+2)
F=(2x+1)-(6x-1)(-3x+8)


Répondre :

Développer et réduire les expressions suivantes.
A=(7x+3)(x+5)
A= 7x²+3x+35x+15
A= 7x²+28x+15

B=(5-2x)(3x-6)
B= 15x-6x²-30+12x
B= -6x²+27x-30

C=(3x+1)(-5x+3)
C= -15x²-5x+9x+3
C= -15x²+4x+3

D=6(x+3)+(2x-3)(3x-5)
D= 6x+18+6x²-9x-10x+15
D= 6x²-13x+33

E=(8-3x)(4x+1)-x(x+2)
E= 32x-12x²+8-3x-x²-2x
E= -13x²+27+8

F=(2x+1)-(6x-1)(-3x+8)
F= 2x+1-(-18x²+3x+48-8)
F= 2x+1+18x²-3x-48+8
F= 18x²-x-39